Implementation and evaluation of whole-course-based Internet Hospital Outpatient Pharmacy Services: a cross-sectional study in western China - Gao, Yangyang; Lv, You; Wang, Shiyan; Guo, Mengran; Guo, Yi; Zheng, Minglin; He, Lulu; Wu, Fengbo; Fan, Ping (Frontiers in Public Health, 2024)
BackgroundIn recent years, the development of telemedicine and eHealth services has led to the rapid worldwide growth of Internet hospitals, which played a significant role during the coronavirus disease 2019 (COVID-19) pandemic. However, little is known about the characteristics and safety of Internet hospital outpatient pharmacy services (IHOPSs), which represent a new model of pharmaceutical services.ObjectiveThis study aimed to reveal the comprehensive characteristics and safety of whole-course-based IHOPSs in a general tertiary hospital in western China.MethodsWe established a whole-course–based IHOPS model. A total of 373,936 online prescriptions placed from February 1, 2020 to January 31, 2023 were analyzed. These included information on patients, prescriptions, and deliveries; error rates for prescription reviews and medication dispensations; economic value; and degree of patient satisfaction. Over the course of the study, a total of 373,936 prescriptions representing 351,884 patients and 945,172 medications were delivered to 22 provinces, 5 autonomous regions, and 4 municipalities in China.ResultsIHOPSs saved patients more than 320,376 days (7,689,036 h) and RMB (Renminbi) ¥94.05 million in costs. The error rates of prescription review and dispensing were 0.0011% and 0.0008%, respectively. The infectious disease department (n = 63,903; 17.09%) ranked first in the number of prescriptions written for all three consecutive years. Of the 373,936 delivered prescriptions, 90.15% (337,104/373,936) were sent to Sichuan.ConclusionThe IHOPS was found to be efficient, convenient, and safe because it handled the challenge of precisely and safely delivering medications to patients on time during and to the end of the COVID-19 pandemic. It provided patients with safe and convenient pharmaceutical services unlimited by geography or time zones. Widespread use of this service could help alleviate pressure on offline pharmacists, giving them the time and resources to provide other professional services. Our model can therefore serve as a useful reference for policymakers to support the development of Internet pharmaceutical services. Further efforts are needed to regulate and standardize the management of this novel service.